PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA PT AGUNG AUTOMALL KUTA - Paripurna, I Gede Diatmika; Supartha, I Wayan Gede; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
The purpose of this study was to analyze the influence of leadership and job satisfaction on turnover intention and its impact on employee’s performance at PT Agung Automall Kuta . The population in this study were all employees of PT Agung Automall Kuta. Sampling technique using quota sampling as many as 71 employees. The research data is primary data obtained from the database of workers and secondary data is vehicle sales. The research instrument used questionnaires and analysis techniques used SEM variants based is Partial Least Square. The results showed that the leadership has positive and significant effect on job satisfaction, leadership has not a significant negative effect on turnover intention, leadership has not positive and significant effect on employee performance, job satisfaction has negative and significant effect on turnover intention, job satisfaction has positive and significant effect on employee performance and turnover intention has negative and significant effect on employees performance of PT Agung Automall Kuta.
Keywords: Leadership, Job Satisfaction, Turnover Intention, Employee Performance